Ideal Trans-Syndesmotic Angle and Syndesmotic Fixation Axis: MR-Based Cross-Sectional Image Analysis - Murat Kaya; Nazım Karahan; Barış Yılmaz; Ahmet Nedim Kahraman; Demet Pepele Kurdal; Hayati Kart (Boğaziçi Tıp Dergisi, 2022)
INTRODUCTION: Malreduction of the syndesmosis is associated with a poor prognosis; recent studies have focused on identifying intraoperative radiological parameters to prevent this phenomenon. Our study aimed to determine easily applicable and reproducible radiological parameters from magnetic resonance image (MRI)-based cross-sectional image analysis in determining the ideal trans-syndesmotic angle (TSA) and syndesmotic fixation axis (SFA). METHODS: A total of 120 ankle MRI scans without osseous/ligamentous injury were performed blindly by an orthopedist and a radiologist. Talar anterior tangent and talar axis line (TAL) were determined by cross-sectional measurements. The bisector of the anterior and posterior tangents of the syndesmotic joint was determined by the SFA, and the TSA was determined by the intersection of SFA and TAL. RESULTS: The average TSA was 16–17°. The SFA was between 28%+-6.6% and 30%+-5.7% anterior to the anteroposterior distance of the tibia laterally and the fibular apex medially. The intraclass correlation coefficient (ICC) range for measurements obtained by observer 1 was 0.600–0.882, while that for those obtained by observer 2 was 0.565-0.904. Interobserver agreement was between 0.589 and 0.901; reliability was acceptable for this new set of measurements. DISCUSSION AND CONCLUSION: Our measurements showed that the ideal TSA was between 16° and 17°, and SFA was located between the fibular apex laterally and the anterior third of the tibia medially. All parameters to be applied should be evaluated on a true lateral radiograph of the ankle because rotation will affect the TSA and the appearance of the SFA in a two-dimensional image.